(untitled) (Tempo e Argumento, 2020)
Claiming the importance of education in the city is a historical demand and an emerging challenge for today’s society, which is charged with ensuring the cultural and educational development of its inhabitants. The History of Education as a scientific discipline, has in its hands the opportunity to develop its own scientific dissemination policy that brings educational historical knowledge closer to society, in order to value the culture of the schoolinvolving citizens in the study and dissemination of educational heritage. Recently history has shown that in the process of socialization and dissemination of knowledge to the community, universities have an important role. This descriptive article attemptsto argue that the educational history research community finds in the university pedagogical museums a new didactic resource to disseminate the historical educational heritage knowledge and develop its sociocultural commitment to society. The work, focusing on the case study of the Pedagogical Museum of the Faculty of Educational Sciences of the University of Seville (Spain), tries to study its role in the development of its dissemination and knowledge transfer function to bring heritage closer educational to those who make up the city, detailing the set of forms, actions and outreachdissemination activities they carry out. It concludes that through these, the museum contributesto foster a historical-educational culture in the citizenship.